GAMBARAN MIKROBIOLOGI ISPA (INFEKSI SALURAN PERNAPASAN ATAS) DI SEKELOMPOK JAMAAH HAJI SURABAYA TAHUN 2004 - Prihatini Prihatini (Indonesian Association of Clinical Pathologist and Medical laboratory, 2005)
Upper respiratory tract infection usually has been presence on hajj pilgrims after they spent at the holy Mecca. They are known by long duration cough until they were come home. The pilgrims have been given health education how to live in Mecca and Medina before they go to Saudi Arabia and had meningitis vaccination as well. The purpose of this study is to know what the cause of the upper respiratory tract infection. If the pathogens have been found, before departure the infected pilgrims have been given antibiotics to prevent the pilgrimage ceremony to be disturbed.. Regarding the infection problems this study will be done, to give information whether the pathogenic that cause URI is from Indonesia or Saudi Arabia. About 118 people partially from Surabaya’s pilgrims were divided into 1st and 2nd groups (53 and 65 persons). Each group have been examined their pharyngeal swab before the departure to Mecca and after arrival in Surabaya. The samples were kept in transport media, than sent to the Clinical Pathologic Laboratory at Dr Soetomo Hospital. The swab samples were isolated and identificated after the cultivation in the incubator at the laboratory. From the118 pilgrims, only 95 persons completed the laboratory examination before the departure to Mekah and after they arrived in Surabaya. It is found before departure 5 person (5%) contaminated by pathogenic microorganism, four from K. pneumoniae and one A betahemolytic Streptococcus group. After their arrival about 97% have normal flora, but two of them contaminated by Gamma Streptococcus regarding to these results it is concluded that URI may cause by the environment, difference of weather or viral infection origin Because in the town at Saudi Arabia the pilgrim lived together with other peoples which came from various countries of the world.